Developing a framework for performance assessment of the public long-term care system in Korea: methodological and policy lessons - Hongsoo Kim; Boyoung Jeon (BMC, 2020)
Abstract Background Limited evidence exists on how to assess long-term care system performance. This study aims to report on the process and results of developing a performance assessment framework to evaluate the long-term care system financed by the public long-term care insurance in South Korea. Methods The framework was developed through a six-step approach, including setting the goals and scope of performance assessment in the given policy context, reviewing existing performance frameworks, developing a framework with a wide range of potential indicators, refining the framework through a series of Delphi surveys and expert meetings, examining the feasibility of generated indicators through a pilot test, receiving the comments of stakeholders, and finalising the performance framework. Results The finalised framework has 4 domains - coverage, quality of care, quality of life and system sustainability - and 28 indicators, including 10 core indicators to monitor long-term care system performance. Usability and feasibility along with policy relevance were important criteria in selecting these indicators. The proposed framework can be used to assess the performance of the long-term care system in Korea, and the framework and its methodological approach can be benchmarks for other countries developing their own framework. Conclusions It is critical to reconcile and prioritise various stakeholders' views and information needs as well as to balance methodological rigor with practical usefulness and feasibility in the development and implementation of a long-term care performance monitoring system.